THE PROCESS OF INCLUSION OF A STUDENT INTELLECTUAL DISABILITY IN A COMMON SCHOOL ELEMENTARY SCHOOL I - Morgado, Camila Lourenco [UNESP]; Fiscarelli, Silvio Henrique [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
Faced with the educational policies that advocate inclusive education that respects and values all students, regardless of their individual characteristics, we developed a study to see how this scenario is seen by a professor of regular school that works with a student with intellectual disabilities in Elementary Education I. for this we used a qualitative research approach, as methodological approach the case study and semi-structured interviews as a data collection instrument. The aim was to analyze the concepts by the teacher on the teaching profession, including the assistance by the management team and the ESA, design student learning disabled and the contact with the family. The data showed that many advances have been achieved in the legal framework regarding the inclusion of students with disabilities in regular schools, but the reality of the classroom is still fragile, which makes the effective inclusion of students with disabilities.
Keywords: School inclusion; Elementary school; Intellectual disabilities; Teaching profession